Educação e relações étnico-raciais : formação docente em curso de filosofia da UFMT - Lima, Jeniffer Regina Rodrigues de (2020)
This dissertation entitled “Education and ethnic-racial relations: teacher training in a philosophy course at UFMT” is linked to the Postgraduate Program in Education (PPGE), at the Federal University of Mato Grosso - UFMT (Campus Cuiabá), in line with research “Social Movements, Politics and Popular Education”. This research, promoted by CAPES, was developed within the scope of the Center for Studies and Research on Race Relations and Education - NEPRE, under the guidance of Professor Dr. Candida Soares da Costa. The object of this research is the Teacher Education in Philosophy in the context of Ethnic-Racial Relations, and, for this, it was decided to analyze the Political-Pedagogical Project of the Course (PPC) as a research source. It is, therefore, a bibliographic (SEVERINO, 2007; GIL, 2010) and documentary (TOLEDO; GONZAGA, 2011) research with a qualitative approach (MINAYO, 2001; GIL, 2010), using the diary as a technique of data collection fieldwork (ARAÚJO, 2013) and content analysis (GODOY, 1995; MINAYO, 2007). The data produced from the PPC seek to understand, through the curriculum, how the education of ethnic-racial relations is contemplated, which are the epistemological bases and which are the frames of reference on human diversity presented in it, that is, who are the philosophers studied in the disciplines. During a journey through Enlightenment Philosophy and the philosophical discourse built about the African in that period, which deprived them of humanity and rationality, it was possible to understand that this same discourse had the consequence of African epistemic denial and the consolidation of European Philosophy as universal. The epistemic racism present in the history of philosophy is reflected in the training curricula, whether at a basic or higher level, even after Law 10.639 / 03 which makes the teaching of Afro-Brazilian and African History and Culture mandatory in school curricula, making it also necessary reflection on teacher education. In 2013, the PPC for a Degree in Philosophy underwent changes, one of which was the adaptation of the curriculum to the Curriculum Guidelines for the Education of Ethnic-Racial Relations, claiming to develop disciplines that address the theme, among them, Ethics, Philosophy of Science, Philosophy and education and teaching practice seminar. After the analysis, the PPC revealed that, even claiming to have an adequate curriculum for the education of ethnic-racial relations, it remains Eurocentric, ignoring African thought and its contribution to the History of Philosophy.